2023
DOI: 10.1021/acs.energyfuels.3c03965
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Surfactant Huff-n-Puff Injection for Enhanced Oil Recovery in Unconventional Reservoirs: An Integrated Experimental and Numerical Simulation Approach Coupled with the HLD-NAC Methodology

Chunhua Lu,
Miao Zhang,
Yilei Hua
et al.

Abstract: Surfactant huff-n-puff (HnP) injection processes have become one of the most attractive enhanced oil recovery (EOR) protocols to effectively produce unconventional oil reservoirs. In this paper, the mechanism of surfactant-enhanced tight oil recovery is comprehensively investigated by experimental and numerical simulation. Imbibition experiments are employed to elucidate the impact of surfactants on enhancing the tight core recovery. Core-scale numerical simulation models are applied to match experimental data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…For the shut-in time influence, no sensitivity was observed from all displacing fluids (see Figure d). The result obtained is similar to those of the previous studies by Cao and Lu, where different periods of shut-in time were investigated, and little changes were observed in the oil production results. This is believed to be due to an indistinguishable pressure buildup when the well is shut in, as exemplified in the previous section (Figure c).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…For the shut-in time influence, no sensitivity was observed from all displacing fluids (see Figure d). The result obtained is similar to those of the previous studies by Cao and Lu, where different periods of shut-in time were investigated, and little changes were observed in the oil production results. This is believed to be due to an indistinguishable pressure buildup when the well is shut in, as exemplified in the previous section (Figure c).…”
Section: Resultssupporting
confidence: 90%
“…Wei investigated a scaling-up to reservoir-scale modeling on a potential of low-salinity water huff-n-puff method, with key factors of injection timing, fluid volume, and a number of cycles found sensitive to the oil production. The authors also realized that the soaking time has no influence on the oil recovery, as found by Sun and Lu, implying that there is suitability of factors in designing the project.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation